1995
DOI: 10.1007/bf02536289
|View full text |Cite
|
Sign up to set email alerts
|

Dietary menhaden oil enhances mitomycin C antitumor activity toward human mammary carcinoma MX‐1

Abstract: In the present study, we investigated the effects of high levels of dietary fish oil on the growth of MX-1 human mammary carcinoma and its response to mitomycin C (MC) treatment in athymic mice. We found that high levels of dietary fish oil (20% menhaden oil + 5% corn oil, w/w) compared to a control diet (5% corn oil, w/w) not only lowered the tumor growth rate, but also increased the tumor response to MC treatment. We also found that high levels of dietary fish oil significantly increased the activities of tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 50 publications
1
46
1
1
Order By: Relevance
“…However, there have been few investigations of the potential use of inducers of DT-diaphorase to enhance the anti-tumour activity of anti-tumour agents that are activated by this enzyme. Shao et al (1995) found that the fish oil menhaden oil increased DT-diaphorase activity in an MX-1, human mammary carcinoma, tumour grown in athymic mice and also increased the response of the tumour xenograft to MMC. We have shown that D3T, an inducer of DT-diaphorase, can increase the level of DT-diaphorase activity in murine lymphoma cells without altering the level of enzyme activity in normal murine marrow cells, resulting in an increase in the anti-tumour activities of MMC and E09 (Begleiter et al, 1996).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, there have been few investigations of the potential use of inducers of DT-diaphorase to enhance the anti-tumour activity of anti-tumour agents that are activated by this enzyme. Shao et al (1995) found that the fish oil menhaden oil increased DT-diaphorase activity in an MX-1, human mammary carcinoma, tumour grown in athymic mice and also increased the response of the tumour xenograft to MMC. We have shown that D3T, an inducer of DT-diaphorase, can increase the level of DT-diaphorase activity in murine lymphoma cells without altering the level of enzyme activity in normal murine marrow cells, resulting in an increase in the anti-tumour activities of MMC and E09 (Begleiter et al, 1996).…”
Section: Discussionmentioning
confidence: 95%
“…A study by Shao et al (1995) found that high levels of dietary fish oil lowered the growth rate of MX-1, human mammary carcinoma, xenografts in athymic mice and increased DT-diaphorase activity in the tumour. The high levels of fish oil also increased the response of the tumour to MMC.…”
mentioning
confidence: 99%
“…We have reported that supplementing the diet of mice with fish oil increased the efficacy of edelfosine against MDA-MB 231 human breast cancer (Hardman et al, 1997), doxorubicin against A549 human lung cancer (Hardman et al, 2000) and CPT-11 against MCF-7 human breast cancer (Hardman et al, 1999a). Other investigators have found that supplementing the diet with omega-3 fatty acids increased the efficacy of: epirubicin against rat mammary tumours (Germain et al, 1999) and cyclophosphamide (Shao et al, 1997) or mitomycin (Shao et al, 1995) against MX-1 human mammary tumours. The results of in vitro studies have shown that a small amount of either eicosapentaenoic acid (EPA) or of docosahexaenoic acid (DHA), the major long chain polyunsaturated fatty acids (PUFAs) found in fish oil, added to cell culture media can cause tumour cell death but not kill cultured normal cells (de Vries and Van Noorden, 1992).…”
Section: Incell Aafamentioning
confidence: 91%
“…In this study, EPA was found to significantly increase the cytotoxicity of isatin towards MDA-MB-231 cells in vitro via modulation of lipid peroxidation. Omega-3 fatty acids have previously been shown to increase the efficacy of various cancer chemotherapy drugs such as doxorubicin [178][179], tamoxifen [180], and mitomycin C [181], as well as radiation therapy [182]. Table 1).…”
Section: Isatins In Combination Therapymentioning
confidence: 99%